Bob the Builder. New to the crew - Hit Entertainment; Twentieth Century Fox Home Entertainment, Inc. (Beverly Hills, Calif. : 20th Century Fox Home Entertainment [distributor], 2007)
Bob and the team have to work on building a bridge, school, and barn. They realize that the best way to finish the projects is with help from their friends Scrambler, Benny, Packer, and the others. They learn that the fun is getting it done!
Title from container.
Originally broadcast on television in 2006.
Not rated.
DVD.
Keywords: Bob the Builder (Fictitious character) -- Juvenile drama; Construction workers -- Juvenile drama; Construction equipment -- Juvenile drama; Friendship -- Juvenile drama; Television programs for children; Television programs for the hearing impaired; Animated television programs